Development of gender advertising - G A Miroshnichenko (RUDN Journal of Studies in Literature and Journalism, 2013)
In article are considered new trends in the functioning of the female gender advertising. Theorized advertising concept, its code, message, allowing to explain the mechanism of creation and successful promotion of new advertising image of a modern woman. Special attention is paid to the specifics of the advertising text, as a tool of formation of the advertising image. Verbal and visual analysis of advertising discourse allowed to reveal, to name and describe the proposed advertising communication female gender images, comment on the effectiveness of their integration into the mass consciousness of the society.